2019
DOI: 10.1038/s41586-019-1785-z
|View full text |Cite|
|
Sign up to set email alerts
|

Bile acid metabolites control TH17 and Treg cell differentiation

Abstract: Users may view, print, copy, and download text and data-mine the content in such documents, for the purposes of academic research, subject always to the full Conditions of use:

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
626
6
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 871 publications
(722 citation statements)
references
References 58 publications
23
626
6
2
Order By: Relevance
“…The effect of isoDCA on dendritic cells in this study is in contrast to recent work of T‐cell‐modulating bile acids, which potentiate Treg generation in a cell‐intrinsic manner 5,6 . This suggests that bile acids have diverse effects on the adaptive immune system and affect multiple cell types, opening the door for further research on how microbial metabolites can influence immune responses.…”
Section: Figurecontrasting
confidence: 76%
See 1 more Smart Citation
“…The effect of isoDCA on dendritic cells in this study is in contrast to recent work of T‐cell‐modulating bile acids, which potentiate Treg generation in a cell‐intrinsic manner 5,6 . This suggests that bile acids have diverse effects on the adaptive immune system and affect multiple cell types, opening the door for further research on how microbial metabolites can influence immune responses.…”
Section: Figurecontrasting
confidence: 76%
“…The molecular mechanism by which the microbiome interacts with peripherally induced Treg (pTreg) is likely complex and multifactorial; however, part of the effect is mediated via the release of microbial fermentation products, such as butyrate and other short‐chain fatty acids 1–3 . In a string of recent studies, a role for host bile acids has also been shown to induce pTreg generation, with this function dependent on commensal colonization 4–6 . In the recent issue of Nature , Rudensky and colleagues dissect the molecular fermentation pathway where the gut microbiome converts an endogenous bile acid into an immunologically active bile acid with the capacity to induce pTreg in the gut 4 …”
Section: Figurementioning
confidence: 99%
“…One of these diseases is ulcerative colitis, an inflammatory bowel disease. Ketogenic diets may dampen inflammation within the gastrointestinal tract by inhibiting the activity of the NLRP3 inflammasome (8), promoting intestinal stem cell regeneration and gut healing (9), and stimulating the release of bile acids that facilitate intestinal immune system homeostasis (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…It is welldocumented that bile acid plays a potent regulation role on intestinal immunity cells [48]. A recently published paper in Nature demonstrated that bile acid metabolites can control Th17 and Treg cell differentiation [49]. In the present study, we found negative associations between hyodeoxycholic acid, isolithocholic acid, and TXB2, which were significantly decreased in the SA group, with serum cytokines, IL-17, TNF-α, and IFN-γ, and positive associations for chenodeoxycholic acid sulfate, L-Carnitine, acetylcholine, and cholic acid metabolites.…”
Section: Discussionmentioning
confidence: 99%